2018
DOI: 10.1038/s41467-018-06541-2
|View full text |Cite
|
Sign up to set email alerts
|

Two high-risk susceptibility loci at 6p25.3 and 14q32.13 for Waldenström macroglobulinemia

Abstract: Waldenström macroglobulinemia (WM)/lymphoplasmacytic lymphoma (LPL) is a rare, chronic B-cell lymphoma with high heritability. We conduct a two-stage genome-wide association study of WM/LPL in 530 unrelated cases and 4362 controls of European ancestry and identify two high-risk loci associated with WM/LPL at 6p25.3 (rs116446171, near EXOC2 and IRF4; OR = 21.14, 95% CI: 14.40–31.03, P = 1.36 × 10−54) and 14q32.13 (rs117410836, near TCL1; OR = 4.90, 95% CI: 3.45–6.96, P = 8.75 × 10−19). Both risk alleles are obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
0
9
0
2
Order By: Relevance
“…Through PICS, the authors identified that about 90% of causal variants are non-coding, with 60% mapping to immunecell enhancers and gained histone acetylation (Farh et al, 2015). McMaster et al (2018) used CHiCAGO, a convolution background model, to analyze significant chromatin interactions between patients with Waldenström macroglobulinemia (WM, ORPHA:33226) and controls in a two-stage GWAS. They identified two high-risk non-coding SNPs, rs116446171 and rs117410836 at 6p25.3 and 14q32.13, respectively.…”
Section: Diagnosis: Mutation Detection And/or Predictionmentioning
confidence: 99%
See 4 more Smart Citations
“…Through PICS, the authors identified that about 90% of causal variants are non-coding, with 60% mapping to immunecell enhancers and gained histone acetylation (Farh et al, 2015). McMaster et al (2018) used CHiCAGO, a convolution background model, to analyze significant chromatin interactions between patients with Waldenström macroglobulinemia (WM, ORPHA:33226) and controls in a two-stage GWAS. They identified two high-risk non-coding SNPs, rs116446171 and rs117410836 at 6p25.3 and 14q32.13, respectively.…”
Section: Diagnosis: Mutation Detection And/or Predictionmentioning
confidence: 99%
“…They identified two high-risk non-coding SNPs, rs116446171 and rs117410836 at 6p25.3 and 14q32.13, respectively. Rs116446171 is located near IRF4, DUSP22, and EXOC2, which are implicated in a variety of lymphoid cancers and might represent an important non-coding variant for WM risk (McMaster et al, 2018). Crippa et al (2014) used a probabilistic HMM applied to human embryonic stem cell (HMES) to identify putative regulatory sequences in ChIP-seq data of a patient with trichorhinophalangeal syndrome (TRPS, ORPHA:324764), a complex autosomal dominant malformative disorder, characterized by distinctive craniofacial and skeletal abnormalities.…”
Section: Diagnosis: Mutation Detection And/or Predictionmentioning
confidence: 99%
See 3 more Smart Citations